Pinocchio in Emojitaliano. Przekład eksperymentalny w kulturze zwrotu wizualnego i performatywnego - Majdzik, Katarzyna (Przekłady Literatur Słowiańskich, 2018)
Pinocchio in Emojitaliano. The Experimental Translation in the Culture of Visual and Performative Turn The article discusses the experimental translation of the classic of children’s literature — Pinocchio (La storia di un burattino) by Carlo Collodi — from Italian into an artificially created language of the emoji signs. The translation was dicussed in the context of other translations of literature into emoji sings and experimental translation in general. This originally new-media translation illustrates the cultural transformations of modernity and can be understood as an expression of the iconic (visual) and performative turn in the humanities. KEY WORDS: Pinocchio, Carlo Collodi, experimental translation, intersemiotic translation, iconic turn, performative turn